How to … assist residents living with visual impairment. (2nd June 2019) - Ashurst, Adrian
Abstract : Many older people will have a degree of sensory impairment. Adrian Ashurst talks about how the care home can make sure all areas are safe for those living with visual impairment or sight loss. He also discusses the benefits of audio books.